Penerapan Pendekatan Pembelajaran Berbasis Proyek Oleh Guru Sekolah Dasar: Studi Kasus Di Indonesia - Basar, Zulfa Rahmani (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2024)
This study aims to explore the implementation of Project-Based Learning (PBL) by teachers in primary schools in Indonesia. PBL has proven to be effective in enhancing 21st-century skills, such as problem-solving, collaboration, and communication. Although many primary schools in Indonesia have started to implement this approach, various challenges remain, including the lack of teacher training and limited resources. This research uses a qualitative approach with case studies in several primary schools in Indonesia, utilizing interviews and observations as data collection methods. The results show that the implementation of PBL has a positive impact on student motivation and engagement in learning, but challenges related to teacher readiness and supporting facilities exist. This study is expected to provide recommendations for improving the effectiveness of PBL implementation in primary schools